Community pharmacy performance evaluation: Reliability and validity of the Pharmacy Patient Questionnaire. (June 2014) - Narayanan, Ajit; Greco, Michael; Reeves, Peter; Matthews, Andrew; Bergin, Jenny
<x content-type="archive" xml:space="preserve">Abstract</x> Objective To evaluate the Pharmacy Patient Questionnaire through a trial study for reliability, validity, and performance evaluation of Australian community pharmacies. Methods A questionnaire measuring 21 evaluative items and 11 questions requesting personal and background information. Four hundred and eighty-two community pharmacies and 20 554 patient responses were included in the analysis. Each patient rated their experience of the pharmacy and interaction with pharmacy staff. Key findings The questionnaire produces reliable data for pharmacies with 35 or more patient responses. Validity was demonstrated through content, construct, and criterion validity. Cluster analysis identified relatively underperforming pharmacies as outliers. Linear regression produced two patient–pharmacy models. The first concerning satisfaction with pharmacy staff showed four items to be important: ability to listen, explanation, initial greeting, and opportunity for expressing concerns. The second concerning satisfaction with the pharmacy overall showed eight items to be important: respect shown by staff, general appearance of the pharmacy, information provided about services, the opportunity for making compliments or complaints, opening hours, staff ability to listen, trustworthy staff, and physical access to the pharmacy. Analysis of variance was used to identify possible demographic effects on overall satisfaction. Conclusions Pharmacies should aim for a minimum of 35 completed patient questionnaires to achieve minimal acceptable reliability of their performance and preferably 45–50 completed patient questionnaires. Overall, the findings in this study support previous findings that interpersonal aspects constitute the most important determinants of satisfaction. General appearance, information about services and physical access are also shown to be important for patient satisfaction with their pharmacies.